A apreensão do bem especulativo como fundamento da moralidade em Tomás de Aquino - Soares, Iago Nicolas de Abreu (2024)
In the following dissertation, we discuss the apprehension of the good that underpins human moral action and how the cognitive method for this apprehension occurs in the thought of Thomas Aquinas. We therefore discuss whether the apprehension of the speculative good, derived from a theoretical reflection of nature and its teleological ordering, serves as a foundation for the apprehension of the first practical principles of natural law, which are based on the apprehension of the human practical good. This problem arises from the debate raised by the New Natural Law Theory and its objections to the then-current interpretation of Thomistic natural law that prevailed until the 20th century. We will employ, as our investigative method, the analysis of S. Th., Ia-IIae, q. 94, a. 2, along with the use of the Corpus Thomisticum as a whole in order to clarify the issues involved in this inquiry. We will also turn to the positions of contemporary commentators on Thomas Aquinas' work in regard to the controversy surrounding natural law, both to respond to objections and to seek support and confirmation for our interpretation.